(untitled) (FACE: Revista de la Facultad de Ciencias Económicas y Empresariales, 2018)
A study of the analysis, and prediction model, was performed on ISA shares, during the period January-March 2018. The objective of the research work was to perform a simple moving average and exponential moving average econometric prediction of ISA stock during the January-March 2018 quarter. A simple moving average and exponential moving average econometric predictive model was run using the Excel package to predict the direction of the share price. It was possible to establish that ISA’s share price in the quarter under study was at 13320, and a forecast of 13160, which represents a decrease in the share price increase, compared to the beginning of the quarter in January 2018, which was 14140.